The Economic Effect of Climate Change on Electricity Use – A Case Study from Cyprus - Hadjinicolaou, Panos; Zachariadis, Theodoros (My University, 2012)
This paper assesses additional electricity requirements and the associated costs in the Mediterranean island of Cyprus because of projected anthropogenic climate change. For this purpose an econometric model of electricity demand is used, in combination with climate projections from a state-of-the-art Global Circulation Model with a regional focus on the Eastern Mediterranean. Results indicate an increase in total power needs by the mid-21st century compared to a „no climate change‟ case. Annual electricity demand is projected to rise by 5.6%, causing annual welfare losses of up to more than 100 million Euros at 2010 prices. Although additional power requirements are not very remarkable on an annual basis, climate change is expected to exacerbate the already existing imbalance between winter and summer electricity demand. This outlook indicates that a reasonable and cost-effective future energy path in regions with Mediterranean climate would involve substantial deployment of solar-powered electricity generation, a zero-carbon energy source that can meet peak load requirements without increasing the country‟s dependency on imported fossil fuels. Moreover, this forecast highlights the need for adaptation to climate change through substantial investments in the improvement of the energy performance of the Mediterranean building stock.
Keywords: Economic Effect; Climate Change; Electricity Use; Cyprus